(untitled) (Polis (Santiago), 2018)
Noting that research on the relationship between medicine and state during the Third Reich has reached an almost exponential development, the article claims that during the Nazi regime medicine was a servile instrument to a subjugation global strategy, targeting both the peoples submitted by force as well as the German people themselves. He notes that terror adduced the arguments to legitimize the extermination of "worthless lives", and led to develop human experiments on the basis of a "rationality of the end of time", where participating doctors seemed to be released of any medical ethics. It can be said that the research on this "medicine without humanity" has profoundly influenced our current view. And the sober realization that it is possible such rupture of ethical boundaries can create social and cultural bases to prevent their recurrence.